2014
DOI: 10.5740/jaoacint.sgemcnabb
|View full text |Cite
|
Sign up to set email alerts
|

First Detection of Tetrodotoxin in the Bivalve Paphies australis by Liquid Chromatography Coupled to Triple Quadrupole Mass Spectrometry With and Without Precolumn Reaction

Abstract: Two methods for the determination of tetrodotoxin (TTX) in marine biota have been developed and validated using ultra-performance LC coupled to triple quadrupole MS. The direct analysis of TTX is completed in one method, while the other method detects the dehydration product of TTX after reaction with base. The methods were validated in a single-laboratory trial and used to test Paphies australis (pipi) samples collected from Whangapoua, New Zealand during April 2011. Pa. australis is a commonly eaten species … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
60
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 3 publications
1
60
3
Order By: Relevance
“…These structures and molecular formula were also proposed as fragment ions of 5,6,11-trideoxyTTX21. In addition, a similar molecule C 9 H 9 N 3 O 2 , molecular weight 191.1, is produced after strong base treatment of TTX15. When the errors between theoretical and experimental data are compared some differences are observed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These structures and molecular formula were also proposed as fragment ions of 5,6,11-trideoxyTTX21. In addition, a similar molecule C 9 H 9 N 3 O 2 , molecular weight 191.1, is produced after strong base treatment of TTX15. When the errors between theoretical and experimental data are compared some differences are observed.…”
Section: Discussionmentioning
confidence: 99%
“…Before 2014 only one highly toxic TTX-accumulation in scallops from Japan had been reported14. However, from 2014 to date three reports have identified the presence of TTX in shellfish and it was also detected in several edible gastropods1516172223. Therefore, the presence of TTXs in shellfish as well as the source of these toxins should be taken into account, since TTX-contaminated samples will not be detected by official analytical methods, such as LC-MS/MS or HLPC with fluorescence detection, because TTX is not required to be included in these methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, sample dilution was performed to improve detection [47]. McNabb et al also reported a method of 1:400 or 1:10000 dilution for the quantitative determination of TTX in paphies australis [48]. In this study, the effect of the volume of the sample extract loaded into the MCX SPE cartridge was studied by measuring the % ME using the post-SPE standard spiking method.…”
Section: Matrix Effects and Optimization Of The Sample Extract Loadinmentioning
confidence: 99%